A study to assess the knowledge of staff nurses regarding kangaroo mother care in Bombay hospital Indore (M.P) - Princy koshy, Ms (International Journal of Nursing Research, 2023)
The main causes of newborn deaths are prematurity and low-birth-weight (WHO May 2012). KMC is a technique of skin-to-skin contact between mothers (or fathers) and their pre-mature infants. Kangaroo mother care restores to mothers their true ownership of their newborns and it restores to newborn their birth right- their right to the best start in life. Aim: The objectives of the study was to assess the level of knowledge regarding kangaroo mother care among staff nurse and find out association between knowledge score and selected demographic variables. Materials and Methods: Explorative research approach was adopted for the study. Convenience sampling was used as sampling technique and 30 female staff nurses working in Bombay Hospital Indore were selected for the study. Data collection was done with help of demographic Performa and structured knowledge questionnaires. Result: Mean value of knowledge level on KMC among staff nurses was 19.6 this value indicates the staff nurses are having moderate knowledge regarding KMC and the value of standard deviation was 2.32. Result shows that there was significant association of knowledge scores with selected demographic variables. Conclusion: The study shows that majority of staff nurses, working in Bombay Hospital, Indore have good knowledge about Kangaroo mother care.